2019
DOI: 10.1177/0141076819877539
|View full text |Cite
|
Sign up to set email alerts
|

The quality and safety of locum doctors: a narrative review

Abstract: SummaryLocum doctors are often perceived to present greater risks of causing harm to patients than permanent doctors. After eligibility and quality assessment, eight empirical and 34 non-empirical papers were included in a narrative synthesis to establish what was known about the quality and safety of locum medical practice. Empirical literature was limited and weak methodologically. Locums enabled healthcare organisations to maintain appropriate staffing levels and allowed staffing flexibility, but they also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(46 citation statements)
references
References 20 publications
2
44
0
Order By: Relevance
“…These findings support earlier calls for the debate about locum doctors and quality to extend beyond the monitoring of locum performance to include the working environment (Ferguson and Walshe 2019, McKevitt et al . 1999).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…These findings support earlier calls for the debate about locum doctors and quality to extend beyond the monitoring of locum performance to include the working environment (Ferguson and Walshe 2019, McKevitt et al . 1999).…”
Section: Discussionsupporting
confidence: 88%
“…Locum doctors are more likely to have complaints made about them than other doctors (General Medical Council 2014) and are often perceived to present a higher risk of causing harm to patients than permanent doctors (Godlee 2010, Isles 2010, Jennison 2013). A recent review found that there was little empirical evidence to show differences in the quality and safety of locum and permanent doctors' practice, and concluded that many of the factors which may plausibly affect the quality and safety of locum practice are more concerned with the way organisations use locums and how they are deployed and supported than with the characteristics of locum doctors themselves (Ferguson and Walshe 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the utilization of locum physicians is pervasive in the USA and the rest of the world, [11][12][13][14][15][16] their outcomes are mostly unknown. [19][20][21] Only one study has investigated locum physician outcomes in patients admitted to IM services (Table 2). 21 The study sample included 38,475 Medicare admissions treated by locum physicians in plurality compared to 1,780,398 admissions treated by IM physicians.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, many believe that locum physicians provide lower patient safety and quality of care. 10,19 However, there are few retrospective studies and no prospective studies investigating care provided by locum physicians in different medical specialties. [19][20][21] Blumenthal et al found that Medicare fee-for-service beneficiaries treated by locum physicians in plurality had similar mortality, higher hospital cost (HC), longer stay, and lower 30-day readmission compared to non-locum internist.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation